The Use of Elecampane (Inula Helenium L.) in the Treatment and Prevention of Diseases of the Plant Supportive Movement System - Babakulovich, Dilmurodov Nasriddin; Norboyevich, Choriyev Otabek; o‘g‘li, Olimjonov Asadbek Qobiljon (American Journal of Biomedicine and Pharmacy, 2025)
This article reviews the scientific evidence justifying the use of elecampane (Inula helenium L.) for the treatment and prevention of musculoskeletal diseases in horses. The plant’s chemical composition and effects on the equine musculoskeletal system were evaluated, particularly its anti-inflammatory, analgesic, and chondroprotective properties. The findings suggest that elecampane is a promising, natural remedy for horses in veterinary medicine.